2015
DOI: 10.1002/cssc.201501399
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of Biomimetic Manganese–Calcium Oxides for Water Oxidation Catalysis—Atomic Structure and Functionality

Abstract: Water-oxidizing calcium-manganese oxides, which mimic the inorganic core of the biological catalyst, were synthesized and structurally characterized by X-ray absorption spectroscopy at the manganese and calcium K edges. The amorphous, birnesite-type oxides are obtained through a simple protocol that involves electrodeposition followed by active-site creation through annealing at moderate temperatures. Calcium ions are inessential, but tune the electrocatalytic properties. For increasing calcium/manganese molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 58 publications
6
61
0
Order By: Relevance
“…Among a variety of other preparation methods, electrodeposition is advantageous as it allows precise control of the formation rate and conditions through control of the applied potential—and consequently the driving force for the film formation. The electrodeposition of catalytically active MnO x has been studied in detail, with the pH of the deposition and testing solution being a variable of importance . While an active catalyst must be functional in water, preparing the catalyst in aqueous solution does impose limits on the conditions applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a variety of other preparation methods, electrodeposition is advantageous as it allows precise control of the formation rate and conditions through control of the applied potential—and consequently the driving force for the film formation. The electrodeposition of catalytically active MnO x has been studied in detail, with the pH of the deposition and testing solution being a variable of importance . While an active catalyst must be functional in water, preparing the catalyst in aqueous solution does impose limits on the conditions applied.…”
Section: Introductionmentioning
confidence: 99%
“…Among av ariety of other preparation methods, [12,14,[23][24][25][26][27] electrodeposition is advantageous as it allows precise control of the formation rate and conditions through control of the appliedp otential-andc onsequentlyt he driving force fort he film formation.T he electrodeposition of catalytically active MnO x has been studied in detail, [16,19,28,29] with the pH of the deposition and testing solution being av ariable of importance. [19,28] While an active catalyst must be functionali nw ater, MnO x films electrodepositedu nder basic, neutral, and acidic conditions from an ionic liquid were investigatedb ym eanso f X-ray absorption spectroscopy at the manganeseL 2,3 -edges and the oxygen K-edge.…”
Section: Introductionmentioning
confidence: 99%
“…The result is an even more disordered manganese oxide with a higher fraction of Mn 3 + ,w hich is most likelyc atalytically more active than Mn 4 + -rich materials. [16,72,82,83] This wasa lso observed in the Raman spectra (Figure S8) recorded for the different MnO x /C anodes after heat treatment, which showedb roader,l ess-intense birnessite features, pointingt oahigher degree of disorder within the structure. In summary,o ur resultss howt hat the optimization of the MnO x deposition times as well as the post-deposition heat treatment is essential for each type of carbon support to obtain efficient anodes.…”
Section: Optimization Of Mno X -Coatedcarbon Substratesmentioning
confidence: 56%
“…[8][9][10][11][12][13][14] Severals tudies have shown that amorphous, layered manganese oxides from the birnessite mineral family are the mostp romising preciousmetal-free OER catalysts, especially for neutral and acidic reaction media. [8,13,15,16] Birnessites consist of layers of edge-sharing [MnO 6 ]o ctahedra with MnÀOa nd MnÀMn distances of approximately 1.9 and 2.9 ,respectively.The distance between two layers is approximately 7 andt he interlayer space can contain varying amountso fw ater and/or additional cations (especially of alkali and earth alkali metals). The average Mn oxidation state in birnessites varies between + 3.3 and + 3.9.…”
Section: Introductionmentioning
confidence: 99%
“…Among the wealth of findings on water oxidation by Mn-based catalysts, here the following two results are of particular importance: (i) Self-assembly of the Mn(III/IV)4CaO5 core in PSII is a light-driven process, involving step-wise oxidation of four solvent Mn 2+ ions by YZ ox coupled to electron transfer to the quinones 19,20 . (ii) Many amorphous Mn oxides of the birnessite type show significant water oxidation activity and share structural as well as functional features with the Mn4CaO5 core of the biological catalyst [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%